(untitled) (Huellas, 2021)
The present work aims to quantify and describe the changes that occurred in land use in the city of Goya, Corrientes province, Argentina, between 1990 and 2016, and to analyze the trends that the changes in land use present in this city in relation to its persistence in gaining, losing or maintaining its current surface. To specify the first point, the gains, losses, net changes, total changes, transitions and exchanges experienced by the different categories of use were calculated, based on the methodology proposed by Pontius, Shusas and Mceachern (2004). These metrics were obtained, on the one hand, by means of a cross-tabulation matrix that compares the two aforementioned years, and on the other, by using the Land Change Modeler (LCM) of the Idrisi Software Selva version. For the analysis of the vulnerability of land use change, the methodology proposed by Braimoh (2006) was used, which is based on the calculation of indices of gains, losses and net changes in relation to the persistence of each class. The results of the work show, firstly, the dynamics that existed in the territory along 26 years in relation to changes in land use; secondly, they present the analysis of the vulnerability that such uses have in relation to winning or losing surface area, that constitutes relevant information when planning the growth of the city.